IntraConnected : MWe (Me + We) as the integration of self, identity, and belonging - Siegel, Daniel J., 1957- (Norton series on interpersonal neurobiology., 2023)
"Who are you? What comprises the essence of what you might call your "self"? How is your identity -- the features that you or others use to define who you are -- currently shaping your experience of belonging? These are not merely academic questions, but may be at the heart of how we can effectively address many of the contemporary challenges we face: the pandemics of racism and social injustice, misinformation and polarization; digital-attention addition; the climate crisis, and even the pandemic of COVID-19. Each of these challenges may be worsened, if not caused by a view of the self as emanating from the body alone: the "solo-self." Learning to adjust our "identity lens" from its narrow focus to a widened view can expand how we experience the self and integrate our features of identity by linking the differentiated body we inhabit with the larger relational world. This broader belong, integrated identity, and synergy of self -- an experience of sensation, perspective, an agency that is larger than its individual parts -- empowers us to recover a more connected and rewarding way of living on Earth. Consistent with the wisdom teachings of Indigenous cultures and contemplative practices from around the globe, science can now join in the message of opening our sense of who we are to address the major challenges of our time. In this way, we are linked to one another as a relational We while being interconnected from the perspective of the individual part, the Me. The integration of Me plus We as a MWe cultivates the experience of being intraconnected with the system as a whole, enabling us to live with a more inclusive sense of self that promotes well-being throughout our individual and collective lives"--